Ethnic and racial differences in self-reported symptoms, health status, activity level, and missed work at 3 and 6 months following SARS-CoV-2 infection - O’Laughlin, Kelli N.; Klabbers, Robin E.; Ebna Mannan, Imtiaz; Gentile, Nicole L.; Geyer, Rachel E.; Zheng, Zihan; Yu, Huihui; Li, Shu-Xia; Chan, Kwun C. G.; Spatz, Erica S.; Wang, Ralph C.; L’Hommedieu, Michelle; et al. (Frontiers in Public Health, 2024)
Introduction: Data on ethnic and racial differences in symptoms and health-related impacts following SARS-CoV-2 infection are limited. We aimed to estimate ethnic and racial differences in symptoms and health-related impacts three and six months after first SARS-CoV-2 infection. Methods: Participants included adults with SARS-CoV-2 infection enrolled in a prospective multicenter US study between 12/11/2020-7/4/2022 as the primary cohort of interest, as well as a SARS-CoV-2-negative cohort to account for non-SARS-CoV-2-infection impacts, who completed enrollment and 3-month surveys (N=3,161; 2,402 SARS-CoV-2-positive, 759 SARS-CoV-2-negative). Marginal odds ratios were estimated using GEE logistic regression for individual symptoms, health status, activity level, and missed work, three and six months after COVID-19 illness, comparing each ethnicity or race to the referent group (non-Hispanic or White), adjusting for demographic factors, social determinants of health, substance use, pre-existing health conditions, SARS-CoV-2 infection status, COVID-19 vaccination status, and survey time point, with interactions between ethnicity or race and time point, ethnicity or race and SARS-CoV-2 infection status, and SARS-CoV-2 infection status and time point. Results: Following SARS-CoV-2 infection, the majority of symptoms were similar over time between ethnic or racial groups. At three months, Hispanic participants were more likely than non-Hispanic participants to report fair/poor health (OR: 1.94; 95%CI: 1.36-2.78) and reduced activity (somewhat less, OR: 1.47; 95%CI: 1.06-2.02; much less, OR: 2.23; 95%CI: 1.38-3.61). At six months, differences by ethnicity were not present. At three months, Other/Multiple race participants were more likely than White participants to report fair/poor health (OR: 1.90; 95% CI: 1.25-2.88), somewhat less activity (OR: 1.72; 1.21-2.46), and much less activity (OR: 2.08; 95%CI: 1.18-3.65). At six months, Asian participants were more likely than White participants to report fair/poor health (OR: 1.88; 95%CI: 1.13-3.12); Black participants reported more missed work (OR, 2.83; 95%CI: 1.60-5.00); and Other/Multiple race participants reported more fair/poor health (OR: 1.83; 95%CI: 1.10-3.05), somewhat less activity (OR: 1.60; 95%CI: 1.02-2.51), much less activity (OR: 2.49; 95%CI: 1.40-4.44) and more missed work (OR: 2.25; 95%CI: 1.27-3.98). Discussion: Awareness of ethnic and racial differences in outcomes following SARS-CoV-2 infection may inform clinical and public health efforts to advance health equity in long-term outcomes.